+0  
 
0
382
1
avatar

what is (l-r)^3

 Jan 5, 2015

Best Answer 

 #1
avatar+21641 
+5

(l - r)3  =  (l - r)(l - r)(l - r)  =  (l - r)[(l - r)(l - r)]  

     =  (l - r)[1 - 2r + r²]                 FOILing (1 - r)(1 - r)

     =  1 - 2r + r² - r + 2r² - r³]      (multiplying out)

     =  1 - 3r  + 3r² - r³                   (simplifying)

 Jan 5, 2015
 #1
avatar+21641 
+5
Best Answer

(l - r)3  =  (l - r)(l - r)(l - r)  =  (l - r)[(l - r)(l - r)]  

     =  (l - r)[1 - 2r + r²]                 FOILing (1 - r)(1 - r)

     =  1 - 2r + r² - r + 2r² - r³]      (multiplying out)

     =  1 - 3r  + 3r² - r³                   (simplifying)

geno3141 Jan 5, 2015

7 Online Users

avatar
avatar